Sedentary Behaviour Patterns and Arterial Stiffness in a Spanish Adult Population - the Evident Trial - Garcia-Hermoso, A (Elsevier Ireland Ltd, 2015)
Objective: Arterial stiffness is a contributor to the development of atherosclerosis and cardiovascular disease. The aim of the study was to analyse the relationship between sedentary behaviour and arterial stiffness in a Spanish adult population. Methods: This cross-sectional study included 1365 subjects belonging to the EVIDENT project. Physical activity and sedentary behaviour were measured objectively over 7 days using ActiGraph accelerometers. Thresholds of 10 consecutive minutes were used to estimate the daily sedentary time in bouts ≥10 min. Each interruption in sedentary time (counts/min ≥100) was considered a break. Arterial stiffness was evaluated using the B-pro device through the following indicators: radial Augmentation Index (rAIx), Ambulatory Arterial Stiffness Index (AASI), and central and peripheral pulse pressure (PP). Results: We found a positive relationship between central and peripheral pulse pressure (office, 24 h, awake and sleep PP) and total sedentary time. These arterial stiffness parameters were also associated with sedentary time in bouts ≥10 min. Significance disappeared in both cases, however, after adjusting for MVPA and breaks per sedentary hour. Adults who reported fewer breaks per sedentary hour (25th percentile < 2 n/day) had higher levels of AASI, awake and sleep PP. Conclusions: In a medium-sized sample of adult attenders of community clinics our data showed that it seems to be important to avoid prolonged uninterrupted periods of sedentary time. © 2015 Elsevier Ireland Ltd.